Deployment of spatial attention without moving the eyes is boosted by oculomotor adaptation - Habchi, Ouazna; Rey, Elodie; Mathieu, Romain; Urquizar, Christian; Farnè, Alessandro; Pélisson, Denis (Frontiers in Human Neuroscience, 2015)
Vertebrates developed sophisticated solutions to select environmental visual information, being capable of moving attention without moving the eyes. A large body of behavioural and neuroimaging studies indicate a tight coupling between eye movements and spatial attention. The nature of this link, however, remains highly debated. Here we demonstrate that deployment of human covert attention, measured in stationary eye conditions, can be boosted across space by changing the size of ocular saccades to a single position via a specific adaptation paradigm. These findings indicate that spatial attention is more widely affected by oculomotor plasticity than previously thought.